Production of Whole-cell Lipase from Aspergillus nomius ST57 and Optimization of Methyl Esters Synthesis from Palm Oil in One Step - Naruemon Rakchai (Science Faculty of Chiang Mai University, 2019)
The production of whole-cell lipase by Aspergillus nomius ST57 for the synthesis of biodiesel (fatty acid methyl esters; FAME) from palm oil was investigated. The whole-cell lipase produced by A. nomius ST57 catalyzed both transesterification and esterification reactions. The whole-cell lipase production in a shake-flask culture was optimized by using Taguchi experimental design and response surface methodology. The optimal culture medium was composed of olive oil 22.91 g/L, yeast extract 10.52 g/L, (NH4)2SO4 1.07 g/L and KH2PO4 1 g/L with the initial pH 5.0. The optimal conditions were 1 mL of 5´106 spores/mL inoculum in 50 mL of medium at 150 rpm and 30 °C for 48 h. The hydrolytic and transesterification activities of the whole-cell lipase were 2 times and 3 times higher than in the non-optimized medium and conditions. The optimal conditions for FAME synthesis by the whole-cell lipase of A. nomius ST57 consisted of 25 mg dry cell weight, palm oil:methanol 1:3 mol/mol and 15% of 50 mM Tris-HCl buffer pH 7 at 37 °C. After 5 h of reaction, 93.54% FAME was obtained in one step addition of methanol.